UPAYA MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN MELALUI MEDIA BIG BOOK PADA SISWA KELAS 1 SEKOLAH DASAR - Ailah; Sutisnawati, Astri; Maula, Luthfi Hamdani (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
The background of this research is that the ability of grade I students of SDN Puncaksuji in reading is still low, which is indicated by the inability of students to sound out syllables and many tetrukar when reading. The purpose of this study was to describe the planning and implementation of learning activities using big book media to improve reading skills and to determine the improvement of reading skills after using big book media. The subjects of this study were first grade students of SDN Puncaksuji, totaling 24 students. The type of research used is classroom action research which consists of four stages, namely planning, implementation, observation, and reflection. The data in this study were collected through tests, observations, and documentation. The data that has been collected is then analyzed using descriptive statistical techniques.